PWE-159 The Costs Of Irritable Bowel Syndrome (ibs) In An Increasingly Cost Aware Nhs. (9th June 2014) - Wilson, P; Poullis, A; Wilkins, J; Rance, M
Abstract : Introduction: The NHS is faced with increasing cost pressures making the efficient use of resources paramount. Both NICE and BSG guidelines state that patients with IBS should be managed in primary care. 1, 2 Despite this up to 50% of patients with a diagnosis of IBS are referred to secondary care for investigation. 3 Outpatient visits and endoscopic investigations consume a considerable NHS resource. Methods: Hospital Episode Statistics (HES) data for 2012–13 for all the Care Commissioning Groups (CCGs) in England were analysed to calculate the financial cost of IBS. IBS symptom codes were included. Organic gastrointestinal (GI) disease codes were excluded from the analysis. Primary Care prescribing analyses and cost (PACT) data 2012–13 were analysed to calculate IBS treatment costs. Results: In England in 2012/13, there were 1, 219, 961 patients attending gastroenterology and colorectal surgery outpatient specialties, with a total cost of £365, 868, 937. Despite this, only a total of 1, 982 patients who were coded as IBS with a total estimated cost of £744, 812 were recorded. However, if we look at the total costs of patients under 50 years of age with excluded diagnosis as described above, we get a total of 28, 849 patients with a cost of £11, 002, 874. In 2011/12, there were also 323, 752 day case and outpatient diagnostic endoscopies with a total cost of £169, 676, 704 where no further activity was seen either as an inpatient or outpatient for the 12 months following the diagnostic endoscopy. This represents 49% of the total diagnostic endoscopies performed in this group of patients. In Primary Care, treatment with laxatives and antispasmodics totalled over 50 million pounds, with £40, 219, 270 spent on macrogol and £11, 024, 948 spent on mebeverine. Conclusion: Despite being poorly clinically coded it is clear that IBS is a significant costs burden to the NHS. Over half of patients seen for day case and outpatient diagnostic endoscopies have no further clinical activity coded over the subsequent 12 months implying functional symptoms. Better diagnosis and subsequent management of IBS within a Primary Care setting would provide direct savings in the cost of IBS management as well as enabling GI services to target its resources such as colonoscopy services towards other GI conditions more appropriately in areas of greater clinical need. Work funded by Almirall as a "Service to Medicine". Hospital Episode Statistics Data provided via Harvey Walsh Ltd under commercial reuse licence from the Health and Social Care Information Centre 2014. References: 1N. I. C. E. IBS in Adults. Clinical Guidelines 61. 2008 2B. S. G. Guidelines on IBS. 2007 3B. S. G. Commissioning Report on IBS. 2009 Disclosure of Interest: P. Wilson: None Declared, A. Poullis: None Declared, J. Wilkins Employee of: Harvey Walsh Ltd, M. Race Employee of: Almirall